PIASγ expression in relation to clinicopathological, tumour factors and survival in indigenous black breast cancer women. Issue 4 (29th October 2013) - Agboola, Ayodeji; Musa, Adewale; Banjo, Adekumbiola; Ayoade, Babatunde; Deji-Agboola, Mopelola; Nolan, Christopher; Rakha, Emad; Ellis, Ian; Green, Andrew
Abstract : Aim: Indigenous black women with breast cancer (BC) show a high frequency of triple negative breast cancer (TNBC) comprising ER-, PR- and HER2- phenotypes and BRCA1 deficiency together with a high mortality rate, prompting speculation that risk factors could be genetic and the molecular portrait of these tumours may be different to those of Western women. Protein inhibitor of activated signal transducer (PIAS) γ implicated in the BRCA1 deficiency and triple negative BC was investigated to establish the relationship among the small ubiquitin-like modifier marker, pathological features, biomarkers expression and clinical outcome in the black women. Materials and methods: This study investigated the immunoprofiles of PIASγ in 231 Nigerian BC prepared as tissue microarrays and correlated their protein expression with clinical outcome, pathological responses and the expression of 14 other relevant biomarkers. Results: PIASγ protein expression showed a significant correlation with higher histological grade, basal-like biomarkers expression (CK14, CK5/6 and EGFR), BRCA1 regulator (MTA1), p53, PI3KCA, basal-like phenotype and TNBC. Also, an inverse correlation with steroid hormones (ER and PgR), p27, MDM4, mucin 1 and BRCA1 was observed with PIASγ expression. Univariate and multivariate survival analyses showed PIASγ expression was a predictor of poor outcome independent of tumour histological grade and ER expression. Conclusions: PIASγ appears to be important in breast cancer behaviour arising from Nigerian women. PIASγ may therefore be useful for the screening of basal-like and TNBC. Also, development of novel therapies towards targeting PIASγ functional pathways may enhance the BC management among this ethnic nationality.